Preclinical and Clinical Pharmacology of Hydrocodone for Chronic Pain: A Mini Review - Cardia, Luigi; Calapai, Gioacchino; Quattrone, Domenico; Mondello, Cristina; Arcoraci, Vincenzo; Calapai, Fabrizio; Mannucci, Carmen; Mondello, Epifanio (Frontiers in Pharmacology, 2018)
Hydrocodone is one of the most prescribed oral analgesic drugs and it is one of the most abused drugs in general population. It is a mu-opioid agonist predominantly metabolized to the O-demethylated product hydromorphone and to the N-demethylated product norhydrocodone. The purpose of the study is to summarise the preclinical and clinical characteristics of hydrocodone. Pharmacokinetic aspect (terminal half-life, maximum serum concentration, and time to maximum serum concentration) of hydrocodone and the influence of metabolic genetic polymorphism in analgesic response to hydrocodone are also illustrated and commented. Literature on experimental preclinical pharmacology investigating analgesic activity in laboratory animals is furtherly discussed. Moreover, the authors discuss and comment on the updated data regarding safety profile and effectiveness of hydrocodone in the treatment of chronic pain. A bibliographic research was carried out (from 01 February 2018 until 28 August 2018) independently by two researchers (blinded to the authors and initially on results) in the major scientific databases and research engines of peer-reviewed literature on life sciences and biomedical topics, starting from January 1990 to August 2018. Analysis of results of clinical studies suggests that abuse-deterrent extended-release (ER) hydrocodone formulations can be effective and they are well tolerated in the treatment of chronic low back pain. Weaker is the evidence of the analgesic effectiveness of ER hydrocodone on other chronic pain syndromes and non-cancer non-neuropathic chronic pain. In these conditions, hydrocodone showed to have positive effects in non-controlled open studies and needs to be further studied to assess the real strength of results.